Bioaugmentation, biostimulation and biocontrol - Singh, Ajay.; Parmar,Nagina; Kuhad, Ramesh C.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Bioaugmentation, biostimulation and biocontrol approaches using microbial inoculants, biofertilizers, biochemicals and organic amendments improve soil biology, fertility and crop productivity by providing plant growth-promoting nutrients and suppressing soil-borne diseases and plant-parasitic nematodes. Our knowledge of microbial diversity and its function in soils has been increased tremendously due to the availability of a wealth of data gained through recent advances in the development of molecular methods and metagenomics for the evaluation of microbial diversity and functions in the rhizosphere environment of soil. Chapters dealing with the application of biofertilizers and organic amendments are contributed by experts - authorities in the area of soil science including microbiology and molecular biology - from academic institutions and the industry.
Ajay Singh, Nagina Parmar, Ramesh C. Kuhad and Owen P. Ward: Bioaugmentation, Biostimulation and Biocontrol in Soil Biology -- Nagina Parmar and Jaimie Dufresne: Beneficial Interactions of Plant Growth Promoting Rhizosphere Microorganisms -- S.S.Dudeja et al.: Biofertilizer Technology and Pulse Production -- Ramesh Chander Kuhad, Surender Singh, Lata and Ajay Singh: Phosphate Solubilizing Microorganisms -- Alok K. Pandey, Brijesh K. Mishra, Anju Arora, Surender Singh, Lata and Ramesh C. Ray: Bioaugmentation and Biovalorization of Agro-food and Beverage Industry Effluents -- Ramesh Chander Kuhad, Piyush Chandna, Lata, Ajay Singh: Composting of Lignocellulosic Waste Material for Soil Amendment -- Thierry Lebeau: Bioaugmentation for In Situ Soil Remediation: How to Ensure the Success of Such a Process -- Iwona Zawierucha and Grzegorz Malina: Bioremediation of Contaminated Soils: Effects of Bioaugmentation and Biostimulation on Enhancing Biodegradation of Oil Hydrocarbons -- Poonam Mudgil: Biosurfactants for Soil Biology -- Anu Kalia and Rajinder K. Mudhar: Biological Control of Pests -- Sudhamoy Mandal and Ramesh C. Ray: Induced Systemic Resistance in Biocontrol of Plant Diseases -- Satyavir S. Sindhu, Y.S. Rakshiya and M.K. Verm: Biological Controlof Termites by Antagonistic Soil Microorganisms -- Ramesh C. Ray, Manas R. Swain, Smita H. Panda and Lata: Microbial Control of Postharvest Diseases of Fruits, Vegetables, Roots and Tubers.  .
Electronic reproduction.
Keywords: Soil microbiology; Plant growth-promoting rhizobacteria; Pests -- Biological control; Electronic books